Efektivitas Pengembangan Media Pembelajaran Game Edukasi Berbasis Baamboozle pada Mata Pelajaran Matematika di SMA Negeri 1 Jalaksana - Nuryanti, Amelia; Nurjanah, Hifni Fitriah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The problem underlying this research is the lack of the use of technology-based learning media in mathematics subjects, the teacher's learning model using conventional teaching methods, and students' difficulties in learning mathematics. This research aims to develop educational game learning media based on Baamboozle for mathematics subjects in class X at SMA Negeri 1 Jalaksana. The study was conducted at SMA Negeri 1 Jalaksana using research and development methods with the ADDIE model, and the subjects were 26 class X students consisting of 6 students for the small group trial and 20 students for the large group trial. The data collection techniques used in this research were validation sheets, student response questionnaires, and documentation. The results of the study showed that: (1) the validity of the media obtained a score of 88% from subject matter experts in the “Very Effective” category and 94% from media experts in the “Very Effective” category; (2) the beta test conducted yielded a result of 76% in beta test 1, categorized as “Good,” and beta test 2 yielded a result of 86%, categorized as “Very Good.” It can be concluded that the development of Baamboozle-based educational game learning media in mathematics is effective for use in learning in class X at SMA Negeri 1 Jalaksana.